2021
DOI: 10.1016/j.cjco.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Nosocomial COVID-19 Infection in Cardiac Surgery: An Uncommon Event With High Mortality Rate

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Vaccination programs and treatment protocols continue to advance, but disease-related hospital admissions remain high. COVID-19 poses significant risk to both patients and hospital staff [4][5][6][7]. There are very few evidence-based guidelines currently published by surgical societies that provide recommendations regarding the surgical management of the COVID-19 patients.…”
Section: Description Of the Health Problemsmentioning
confidence: 99%
“…Vaccination programs and treatment protocols continue to advance, but disease-related hospital admissions remain high. COVID-19 poses significant risk to both patients and hospital staff [4][5][6][7]. There are very few evidence-based guidelines currently published by surgical societies that provide recommendations regarding the surgical management of the COVID-19 patients.…”
Section: Description Of the Health Problemsmentioning
confidence: 99%
“…15 Similarly, a lower frequency of nosocomial COVID-19, ranging from 0% to 1.4%, has been described. 16,17 However, studies from Wuhan and London in 2020 reported a higher proportion (12.3% and 11%, respectively) of patients presumed to have nosocomial COVID-19. 5,11 The lower frequency in this study could be explained by several reasons.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, the length of stay for patients with nosocomial SARS-CoV-2 infection has ranged from 2.2 to 52 days. 15,16,18 However, comparisons with patients without nosocomial COVID-19 have not been described. In a study conducted in a stroke/neurology ward in the United Kingdom, Jewkes stated that the mean age of cases with nosocomial COVID-19 was 75 years.…”
Section: Resultsmentioning
confidence: 99%
“…2 patients required admission to the ICU and subsequently died. Wound dehiscence and mediastinitis occurred in a patient who stayed in the hospital for 52 days [ 8 ]. Silveira et al report a case of coronary artery bypass surgery tested positive for COVID-19 on POD 9.…”
Section: Discussionmentioning
confidence: 99%